Epimeria of the Southern Ocean with notes on their relatives (Crustacea, Amphipoda, Eusiroidea) - d'Udekem d'Acoz, Cédric; Verheye, Marie L. (European Journal of Taxonomy, 2017)
The present monograph includes general systematic considerations on the family Epimeriidae, a revision of the genus Epimeria Costa in Hope, 1851 in the Southern Ocean, and a shorter account on putatively related eusiroid taxa occurring in Antarctic and sub-Antarctic seas. The former epimeriid genera Actinacanthus Stebbing, 1888 and Paramphithoe Bruzelius, 1859 are transferred to other families, respectively to the Acanthonotozomellidae Coleman & J.L. Barnard, 1991 and the herein re-established Paramphithoidae G.O. Sars, 1883, so that only Epimeria and Uschakoviella Gurjanova, 1955 are retained within the Epimeriidae Boeck, 1871. The genera Apherusa Walker, 1891 and Halirages Boeck, 1891, which are phylogenetically close to Paramphithoe, are also transferred to the Paramphithoidae. The validity of the suborder Senticaudata Lowry & Myers, 2013, which conflicts with traditional and recent concepts of Eusiroidea Stebbing, 1888, is questioned. Eight subgenera are recognized for Antarctic and sub-Antarctic species of the genus Epimeria: Drakepimeria subgen. nov., Epimeriella K.H. Barnard, 1930, Hoplepimeria subgen. nov., Laevepimeria subgen. nov., Metepimeria Schellenberg, 1931, Pseudepimeria Chevreux, 1912, Subepimeria Bellan-Santini, 1972 and Urepimeria subgen. nov. The type subgenus Epimeria, as currently defined, does not occur in the Southern Ocean. Drakepimeria species are superficially similar to the type species of the genus Epimeria: E. cornigera (Fabricius, 1779), but they are phylogenetically unrelated and substantial morphological differences are obvious at a finer level. Twenty-seven new Antarctic Epimeria species are described herein: Epimeria (Drakepimeria) acanthochelon subgen. et sp. nov., E. (D.) anguloce subgen. et sp. nov., E. (D.) colemani subgen. et sp. nov., E. (D.) corbariae subgen. et sp. nov., E. (D.) cyrano subgen. et sp. nov., E. (D.) havermansiana subgen. et sp. nov., E. (D.) leukhoplites subgen. et sp. nov., E. (D.) loerzae subgen. et sp. nov., E. (D.) pandora subgen. et sp. nov., E. (D.) pyrodrakon subgen. et sp. nov., E. (D.) robertiana subgen. et sp. nov., Epimeria (Epimeriella) atalanta sp. nov., Epimeria (Hoplepimeria) cyphorachis subgen. et sp. nov., E. (H.) gargantua subgen. et sp. nov., E. (H.) linseae subgen. et sp. nov., E. (H.) quasimodo subgen. et sp. nov., E. (H.) xesta subgen. et sp. nov., Epimeria (Laevepimeria) anodon subgen. et sp. nov., E. (L.) cinderella subgen. et sp. nov., Epimeria (Pseudepimeria) amoenitas sp. nov., E. (P.) callista sp. nov., E. (P.) debroyeri sp. nov., E. (P.) kharieis sp. nov., Epimeria (Subepimeria) adeliae sp. nov., E. (S.) iota sp. nov., E. (S.) teres sp. nov. and E. (S.) urvillei sp. nov. The type specimens of E. (D.) macrodonta Walker, 1906, E. (D.) similis Chevreux, 1912, E. (H.) georgiana Schellenberg, 1931 and E. (H.) inermis Walker, 1903 are re-described and illustrated. Besides the monographic treatment of Epimeriidae from the Southern Ocean, a brief overview and identification keys are given for their putative and potential relatives from the same ocean, i.e., the Antarctic and sub-Antarctic members of the following eusiroid families: Acanthonotozomellidae Coleman & J.L. Barnard, 1991, Dikwidae Coleman & J.L. Barnard, 1991, Stilipedidae Holmes, 1908 and Vicmusiidae Just, 1990. This overview revealed the existence of a new large and characteristic species of Alexandrella Chevreux, 1911, A. chione sp. nov. but also shows that the taxonomy of that genus remains poorly known and that several ‘variable widespread eurybathic species’ probably are species complexes. Furthermore, the genera Bathypanoploea Schellenberg, 1939 and Astyroides Birstein & Vinogradova, 1960 are considered to be junior synonyms of Alexandrella. Alexandrella mixta Nicholls, 1938 and A. pulchra Ren in Ren & Huang, 1991 are re-established herein, as valid species. It is pointed out that this insufficient taxonomic knowledge of Antarctic amphipods impedes ecological and biogeographical studies requiring precise identifications. Stacking photography was used for the first time to provide iconographic support in amphipod taxonomy, and proves to be a rapid and efficient illustration method for large tridimensionally geometric species. A combined morphological and molecular approach was used whenever possible for distinguishing Epimeria species, which were often very similar (albeit never truly cryptic) and sometimes exhibited allometric and individual variations. However in several cases, taxa were characterized by morphology only, whenever the specimens available for study were inappropriately fixed or when no sequences could be obtained. A large number of Epimeria species, formerly considered as eurybathic and widely distributed, proved to be complexes of species, with a narrower (overlapping or not) distribution. The distributional range of Antarctic Epimeria is very variable from species to species. Current knowledge indicates that some species from the Scotia Arc and the tip of the Antarctic Peninsula are narrow range endemics, sometimes confined to one island, archipelago, or ridge (South Georgia, South Orkney Islands, Elephant Island or Bruce Ridge); other species have a distribution encompassing a broader region, such as the eastern shelf of the Weddell Sea, or extending from the eastern shelf of the Weddell Sea to Adélie Coast. The most widely distributed species are E. (D.) colemani subgen. et sp. nov., E. (E.) macronyx (Walker, 1906), E. (H.) inermis Walker, 1903 and E. (L.) walkeri (K.H. Barnard, 1930), which have been recorded from the Antarctic Peninsula/South Shetland Islands area to the western Ross Sea. Since restricted distributions are common among Antarctic and sub-Antarctic Epimeria, additional new species might be expected in areas such as the Kerguelen Plateau, eastern Ross Sea, Amundsen Sea and the Bellingshausen Sea or isolated seamounts and ridges, where there are currently no Epimeria recorded. The limited distribution of many Epimeria species of the Southern Ocean is presumably related to the poor dispersal capacity in most species of the genus. Indeed with the exception of the pelagic and semi-pelagic species of the subgenus Epimeriella, they are heavy strictly benthic organisms without larval stages, and they have no exceptional level of eurybathy for Antarctic amphipods. Therefore, stretches deeper than 1000 m seem to be efficient geographical barriers for many Epimeria species, but other isolating factors (e.g., large stretches poor in epifauna) might also be at play. The existence of endemic shelf species with limited dispersal capacities in the Southern Ocean (like many Epimeria) suggests the existence of multiple ice-free shelf or upper slope refugia during the Pleistocene glaciations within the distributional and bathymetric range of these species. Genera with narrow range endemics like Epimeria would be excellent model taxa for locating hotspots of Antarctic endemism, and thus potentially play a role in proposing meaningful Marine Protected Areas (MPAs) in the Southern Ocean.